Arkaisme dalam bahasa Melayu: suatu tinjauan dari aspek kosa kata dalam teks klasik (Jurnal Bahasa, 2008)
Archaism is an interesting and intriguing facet of language. Therefore, this article is another attempt to trace some of the characteristics of archaic words found in old texts like Sejarah Melayu, Hikayat Malim Deman, and Hikayat Hang Tuah. Besides identifying these 'old-fashioned' words, this study recognizes the characteristics of these archaic words. Archaism portrays its resourcefulness in formulating and coining new words and terms in the Malay language. Now, some of these words have found their way into the modern Malay vocabulary after undergoing some phonological and morphological changes. Archaism though considered obsolete, but do still exists in old classical Malay texts, old Malay literature, poetry, religious texts, and in some law books.